Two new species of Neoperla montivaga group (Plecoptera: Perlidae) from Guangxi Zhuang Autonomous Region of southern China - Li, Weihai; Mo, Raorao; Wang, Guoquan (Zootaxa, 2020)
Two new stonefly species of the Neoperla montivaga species group, N. delphina sp. nov. and N. quadrispina sp. nov. are described from the Guangxi Zhuang Autonomous Region of southern China and compared with other taxa of the diehli subgroup.